GAMBARAN HASIL PENGOBATAN TBC PADA LANSIADI PUSKESMAS GOMBONG I - Yuda, Hendri Tamara; Rosa, Elsye Maria; Khoiriyati, Azizah (Jurnal Ilmiah Kesehatan Keperawatan, 2015)
Life expectancy becomes higher and higher is one of successful indicators in development. Pulmonary system diseases, especially tuberculosis is the common disease that attacks elderly. The aim of this research is Obtaining comprehension about tuberculosis treatment result in elderly This research used retrospective study using non-experimental descriptive analysis designThe treatment results of the tuberculosis sufferer in Gombong Public Health Center is about 50% elderly had recovered from tuberculosis, 18,75% of elderly passed away, 6,25% moved to other health center and 6,25% had dropped out of drugs / default. There are 4 themes identified from the family consist of changes the elderly, the ability to carry out the health task of family, life quality, values and beliefs in caring for the elderly with tuberculosis. Keywords: family, caring, elderly, tuberculosis.